2022
DOI: 10.3389/fenvs.2022.969819
|View full text |Cite
|
Sign up to set email alerts
|

Conservation tillage and residue management improve soil health and crop productivity—Evidence from a rice-maize cropping system in Bangladesh

Abstract: The rice-maize (R-M) system is rapidly expanding in Bangladesh due to its greater suitability for diverse soil types and environments. The present conventional method of cultivating puddled transplanted rice and maize is input-intensive, decreases soil health through intense ploughing, and ultimately reduces farm profitability. There is a need to investigate alternatives. Accordingly, we conducted a replicated 2-year (2020–2021) field study to investigate the effects of conservation agriculture (CA) based till… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…Although soil's light POM fraction was increased resulting from short-term experiment conducted, however, soil BD revealed enhanced soil compaction. Conversely, Sarker et al (2022) reported that an increase in the soil light POM revealed an impact on soil compaction causing an enhancement in the soil porosity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although soil's light POM fraction was increased resulting from short-term experiment conducted, however, soil BD revealed enhanced soil compaction. Conversely, Sarker et al (2022) reported that an increase in the soil light POM revealed an impact on soil compaction causing an enhancement in the soil porosity.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, Sarker et al. (2022) reported that an increase in the soil light POM revealed an impact on soil compaction causing an enhancement in the soil porosity.…”
Section: Discussionmentioning
confidence: 98%